Modelling, Dimensioning and Optimization of 5G Communication Networks, Resources and Services - Moscholios, Ioannis D.; Głąbowski, Mariusz; Sarigiannidis, Panagiotis; Logothetis, Michael D. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint aims to collect state-of-the-art research contributions that address challenges in the emerging 5G networks design, dimensioning and optimization. Designing, dimensioning and optimization of communication networks resources and services have been an inseparable part of telecom network development. The latter must convey a large volume of traffic, providing service to traffic streams with highly differentiated requirements in terms of bit-rate and service time, required quality of service and quality of experience parameters. Such a communication infrastructure presents many important challenges, such as the study of necessary multi-layer cooperation, new protocols, performance evaluation of different network parts, low layer network design, network management and security issues, and new technologies in general, which will be discussed in this book.